Integrated platform for Agriculture in India using ICT platform mGAP :Survey - *, Ayonija; Singh, Deepak (IJRDO -Journal of Computer Science Engineering, 2016)
This project is going to develop to improve qualityof food material and farmer growth. This platform willprovide better product through farm by using bestpractices and Agro-Expert advisory system to Farmerthrough mGAP®. So this best agriculture practice and AgroExpertsuggestion will help the farmer to develop betterquality of product and will standalone at global market.